The Relationship between Academic Life Satisfaction and Suicidal Ideation in College Students - Hamidah, Empi Wanda; Eryandra, Alvin (ARISTO, 2025)
Information regarding students ending their lives often occurs. The decision to end one's life is often associated with an unstable and likely poor mental health condition. There are several factors that influence health or mental condition, one of them is current life experiences. For individuals who have the status of university students, of course college life is a meaningful thing during college. The experience of campus academic life is an important aspect that involves students' feelings and actions. In college life, students are involved in social relationships with the academic community and involved in various learning activities. Recurrent incidents of student suicide require identifying various predictors of the reasons behind the decision, in order to find inclusive solutions in preventing similar incidents. The aim of this research is to look at the relationship between Academic Life Satisfaction and Suicide Ideation in students. The research method used is a quantitative method with the Spearman's rho correlation test. The research data came from respondents totaling 289 active undergraduate students who filled out the ALSS (Academic Life Satisfaction Scale) and SIS (Suicide Ideation Scale) questionnaires. The results showed a significant negative relationship with an r value of -0.209 and p 0.000 (<0.10), which means that the higher the level of student satisfaction with their academic life, the lower the frequency of thoughts of ending their life.